Jamaica : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report ;, 2022)
Jamaica was hit hard by the pandemic. An early lockdown in the Spring of 2020 helped contain the number of Covid-19 cases but the impact on the economy was severe, with real GDP shrinking by 10 percent. To counter the social and economic effects of the pandemic, the government temporarily reduced the fiscal balance target from +0.7 to -3 percent of GDP, increased spending on health and social protection and reduced the VAT rate. The central bank injected liquidity and encouraged loan moratoria to provide temporary support to the private sector. Growth is expected to rebound to 4.7 percent in 2021 and 4.3 percent in 2022. Downside risks to the outlook are significant, notably from Covid-19.